2024
DOI: 10.3390/catal14010049
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Mechanism of Reduction of N2O by CO over Fe-ZSM-5 Zeolites

Ning Yuan,
Congru Gao,
Xiuliang Sun
et al.

Abstract: Nitrous oxide (N2O) is an industrial waste gas (e.g., from the production of adipic acid), which damages the ozone layer and causes the greenhouse effect. Density functional theory calculations were employed to investigate the mechanism of direct catalytic decomposition of N2O and selective catalytic reduction (SCR) of N2O by CO over Fe-ZSM-5 zeolites. Two stable Fe-active sites with six-membered ring structures on Fe-ZSM-5 were considered. The calculations indicate that the decomposition of N2O is affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Identifying the precise location of isolated Fe species within the zeolite framework is crucial for comprehending the formation of single-site Fe; however, it remains a challenge. It also highlights previous attempts using density functional theory (DFT) calculations to analyze the preferred sites of Fe species within the zeolite extra-framework . Li and coworkers investigated the localization of isolated [Fe III O] + species stabilized within the ZSM-5 framework.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying the precise location of isolated Fe species within the zeolite framework is crucial for comprehending the formation of single-site Fe; however, it remains a challenge. It also highlights previous attempts using density functional theory (DFT) calculations to analyze the preferred sites of Fe species within the zeolite extra-framework . Li and coworkers investigated the localization of isolated [Fe III O] + species stabilized within the ZSM-5 framework.…”
Section: Resultsmentioning
confidence: 99%
“…It also highlights previous attempts using density functional theory (DFT) calculations to analyze the preferred sites of Fe species within the zeolite extra-framework. 43 Li and coworkers investigated the localization of isolated [Fe III O] + species stabilized within the ZSM-5 framework. Their findings revealed that, at the high spin state, the most stable configuration of isolated [Fe III O] + occurs at the δ site with the [AlO 2 ] − unit at the T-11 position due to the lowest free energy.…”
Section: Synthesis and Characterization Of The Fe Single Sitesmentioning
confidence: 99%